Building Place Branding of Kampung Cabe with Community at Desa Kabasiran Parung Panjang - Andriyani Hapsari; Nani Nani (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
Building a Tourism Village for Kampung Cabe in Kabasiran Village, is a community initiative that grows from their concern for enhancing economic welfare. However, its existence in the past two years has not had a significant effect. There are still many people who do not know Kampung Cabe and are influenced by the image of Kabasiran Village which is associated with poverty. This study aims to formulate strategy for Kampung Cabe to build strong place branding. This research is using a qualitative method with exploratory approach. Data collected by observation, interviews, questionnaires and study literature. The result is to build a strong place branding for Kampung Cabe, there are three steps namely redefining the identity of the values and products that would be conveyed, increase community participation in developing place branding and build pentahelix partnership between government, society, acedemics, business, and media.